Viscoplastic properties of pressure-less sintered silver materials using indentation. (July 2017) - Leslie, D.; Dasgupta, A.; Morillo, Carlos
Abstract: This paper focuses on using a combination of indentation and FEA methods for characterizing the viscoplastic behavior of heterogeneous materials which pose additional challenges because of the non-uniform morphology. In particular, the paper focuses on two forms of pressure-less sintered silver interconnect materials: an adhesive-based particulate composite for low temperature applications and a porous sintered version for high-temperature applications. By using two different post-processing methods (an analytic approach and a computational FEA approach) for the indentation results, we obtain lower and upper estimates to the viscoplastic properties for both of these heterogeneous morphologies. Two types of indenters, spherical and Berkovich, and two types of indentation tests, constant load and constant strain rate, are compared, with regard to their ability to measure the viscoplastic properties of heterogeneous materials. Highlights: Indentation methods to measure viscoplastic properties of porous materials Combination of empirical and numerical methods to estimate viscoplastic parameters Comparison of spherical and Berkovich indenters for porous materials Comparison between constant load and constant strain-rate indentation tests